PERJUANGAN EMANSIPASI WANITA YANG NAIF DALAM KALAU TAK UNTUNG DAN KEHILANGAN MESTIKA - Haniah Haniah (Sawo Manila, 2010)
In general, novels describe about forced marriage which suffered women also pictured in two novels, Kalau Tak Untung, and Kehilangan Mestika. In this matter, the meaning and moral messages of both novels will be analyzed through reconstruction and reflection towards the novel as an effort to appreciate it.Kalau Tak Untung which is absolute in love story, or Kehilangan Mestika which is absolute in tolerances are thesis, but both are also antithesis from the tolerances are thesis, but both are also antithesis from the previous book association, such as Siti Nurbaya dan Azab dan Sengsara. Siti Nurbaya dan Azab dan sengsara.